KEBIJAKAN PEMIDANAAN KORPORASI DALAM TINDAK PIDANA PENCUCIAN UANG - Ginting, Sakeus (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 1 No 1 (2012)DO - 10.24843/JMHU.2012.v01.i01.p05, 2012)
This research aims to analyze the corporation as a legal subject and conviction of the corporation in money laundering. The type of this research is a normative juridical research. Approach to the problem approach with statue approach, analytical and conceptual approach, historical approach and comparative approach. Sources of legal materials used is the primary legal materials and secondary legal materials. Analysis of legal materials be descriptive-analytical, evaluative, interpretive, systematic, comparative and argumetatif. In The Act No. 8 of 2010 concerning Prevention and Eradication of Money Laundry, the Corporation declared as a legal subject that can be held accountable in money laundering. Criminal convictions for corporations may be imposed against the corporation if the criminal offense of money laundering performed or ordered by the personnel control corporation; carried out in order to meet the intent and objectives of the corporation; conducted in accordance with the duties and functions of the perpetrator or the command, and done with the intent to benefit the corporation.
Keywords: corporation, money laundry, conviction, legal subject